SM22α (Smooth Muscle 22α) Prevents Aortic Aneurysm Formation by Inhibiting Smooth Muscle Cell Phenotypic Switching Through Suppressing Reactive Oxygen Species/NF-κB (Nuclear Factor-κB). Issue 1 (January 2019) - Zhong, Lintao; He, Xiang; Si, Xiaoyun; Wang, He; Li, Bing; Hu, Yinlan; Li, Mengsha; Chen, Xiaoqiang; Liao, Wangjun; Liao, Yulin; Bin, Jianping
Abstract : Objective—: Vascular smooth muscle cell phenotypic transition plays a critical role in the formation of abdominal aortic aneurysms (AAAs). SM22α (smooth muscle 22α) has a vital role in maintaining the smooth muscle cell phenotype and is downregulated in AAA. However, whether manipulation of the SM22α gene influences the pathogenesis of AAA is unclear. Here, we investigated whether SM22α prevents AAA formation and explored the underlying mechanisms. Approach and Results—: In both human and animal AAA tissues, a smooth muscle cell phenotypic switch was confirmed, as manifested by the downregulation of SM22α and α-SMA (α-smooth muscle actin) proteins. The methylation level of the SM22α gene promoter was dramatically higher in mouse AAA tissues than in control tissues. SM22α knockdown in ApoE −/− (apolipoprotein E–deficient) mice treated with Ang II (angiotensin II) accelerated the formation of AAAs, as evidenced by a larger maximal aortic diameter and more medial elastin degradation than those found in control mice, whereas SM22α overexpression exerted opposite effects. Similar results were obtained in a calcium chloride-induced mouse AAA model. Mechanistically, SM22α deficiency significantly increased reactive oxygen species production and NF-κB (nuclear factor-κB) activation in AAA tissues, whereas SM22α overexpression produced opposite effects. NF-κB antagonist SN50 or antioxidant N-acetyl-L-cysteine partially abrogated the exacerbating effects of SM22α silencing on AAA formation. Conclusions—: SM22α reduction in AAAs because of the SM22α promoter hypermethylation accelerates AAA formation through the reactive oxygen species/NF-κB pathway, and therapeutic approaches to increase SM22α expression are potentially beneficial for preventing AAA formation. Abstract : Supplemental Digital Content is available in the text.